Urine interleukin-9 and tumor necrosis factor-α for prognosis of human acute interstitial nephritis. Issue 10 (28th October 2020) - Moledina, Dennis G; Wilson, F Perry; Kukova, Lidiya; Obeid, Wassim; Luciano, Randy; Kuperman, Michael; Moeckel, Gilbert W; Kashgarian, Michael; Perazella, Mark A; Cantley, Lloyd G; Parikh, Chirag R
Abstract: Background: We previously demonstrated that urine interleukin (IL)-9 and tumor necrosis factor (TNF)-α can distinguish acute interstitial nephritis (AIN) from other causes of acute kidney injury. Here we evaluated the role of these biomarkers to prognosticate kidney function in patients with AIN. Methods: In a cohort of participants with biopsy-proven, adjudicated AIN, we tested the association of histological features and urine biomarkers (IL-9 and TNF-α) with estimated glomerular filtration rate measured 6 months after diagnosis (6 m-eGFR) controlling for eGFR before AIN and albuminuria. We also evaluated subgroups in whom corticosteroid use was associated with 6 m-eGFR. Results: In the 51 (93%) of the 55 participants with complete data, median (interquartile range) eGFR before and 6 m after AIN were 41 (27–69) and 28 (13–47) mL/min/1.73 m 2, respectively. Patients with higher severity of interstitial fibrosis had lower 6 m-eGFR, whereas those with higher tubulointerstitial infiltrate had higher 6 m-eGFR. IL-9 levels were associated with lower 6 m-eGFR only in the subset of patients who did not receive corticosteroids [6m-eGFR per doubling of IL-9, −6.0 (−9.4 to −2.6) mL/min/1.73 m 2 ]. Corticosteroid use was associated with higher 6 m-eGFR [20.9 (0.2, 41.6) mL/min/1.73 m 2 ] only in those with urine IL-9 above the median (>0.66 ng/g) but not in others. Conclusions: Urine IL-9 was associated with lower 6 m-eGFR only in participants not treated with corticosteroids. Corticosteroid use was associated with higher 6 m-eGFR in those with high urine IL-9. These findings provide a framework for IL-9-guided clinical trials to test efficacy of immunosuppressive therapy in patients with AIN. Graphical Abstract: